2020
DOI: 10.1002/clc.23535
|View full text |Cite
|
Sign up to set email alerts
|

Association of muscular fitness with rehospitalization for heart failure with reduced ejection fraction

Abstract: Background Limited information is available regarding the prognostic potential of muscular fitness parameters in heart failure (HF) with reduced ejection fraction (HFrEF). Hypothesis We aimed to investigate the predictive potential of knee extensor muscle strength and power on rehospitalization and evaluate the correlation between exercise capacity and muscular fitness in patients newly diagnosed with HFrEF. Methods Ninety nine patients hospitalized with a new diagnosis of HF were recruited (64 men; aged 58.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In particular, patients with HF experience easy fatigability of the lower extremities, 29 which leads to limitations in exercise and mobility. In addition, knee extensor muscle power in patients with HFrEF is an independent predictor of HF rehospitalization 17 . However, similar to handgrip strength, muscular strength and power of the lower extremities did not significantly differ between the degrees of the frailty of the K‐FRAIL scale.…”
Section: Discussionmentioning
confidence: 82%
“…In particular, patients with HF experience easy fatigability of the lower extremities, 29 which leads to limitations in exercise and mobility. In addition, knee extensor muscle power in patients with HFrEF is an independent predictor of HF rehospitalization 17 . However, similar to handgrip strength, muscular strength and power of the lower extremities did not significantly differ between the degrees of the frailty of the K‐FRAIL scale.…”
Section: Discussionmentioning
confidence: 82%
“…Kono et al reported that knee extensor muscle strength is an independent factor determining exercise capacity, especially in elderly HF patients with sarcopenia, and provided useful information on exercise prescription 35) . Knee extensor muscle power is an independent predictor for rehospitalization in HF patients with reduced ejection fraction 36) . Therefore, physical therapists need to focus on improving knee extensor muscle strength in patients with HF.…”
Section: Discussionmentioning
confidence: 98%
“…Treadmill training was continued on the regular floor until the patient could ambulate with minimum support (FAC-score 2). In an intention to treat analysis (ITT), the median time to independent ambulation was 6 (3-9) days in the intervention group and 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) days in the UC group (P 5 .063). The authors noted that although not significant in the ITT analysis, the difference in time to independent ambulation was considerable between the intervention and UC group, because of the large hazard ratio (1.97) and Kaplan-Meier curve.…”
Section: Critical Carementioning
confidence: 99%
“…Resistance training is an important method for improving lean muscle mass; however, there is limited evidence for optimal RT prescription because of a low number of studies. A study by Lee et al 9 indicated that knee extensor power is an independent predictor of rehospitalization in patients with HFrEF. Overall, RT can be used as an appropriate intervention in patients with HF, as an adjunct to AT or for those who cannot tolerate AT.…”
Section: Heart Failurementioning
confidence: 99%